The Art Of Advocacy For Victims Of Sexual Violence - Wiwin Ariesta; Sukron, Ahmad; Nabila Dwi Elsa (Al-Zayn: Jurnal Ilmu Sosial, Hukum & Politik, 2025)
Legal advocacy constitutes a vital instrument in the provision of legal aid. The rising number of cases of sexual violence against women and children underscores the necessity of legal advocacy in addressing the needs of victims. The growing number of reported cases of sexual violence should be regarded positively, as it reflects increasing public courage to report such incidents within their communities. Although advocacy does not constitute a legal revolution, its implementation plays a pivotal role in safeguarding the rights of victims of sexual violence. Accordingly, advocacy techniques and methods developed within the community must be examined and evaluated to ensure that their application does not inadvertently harm victims or infringe upon their rights. The practice of advocacy must therefore be continuously refined and adapted to the specific needs of those who receive advocacy services in this context, victims of sexual violence. This study employs a normative legal research method, supported by empirical legal research based on cases of sexual violence within the jurisdiction of Pasuruan Regency. The findings suggest that several advocacy techniques generally applied in other contexts may also be effectively implemented in providing legal aid for victims of sexual violence. Nevertheless, the involvement of relevant stakeholders and the allocation of adequate resources are essential to promoting victims’ well-being. Confidentiality must likewise be strictly observed as an integral part of protecting victims of sexual violence. Furthermore, the adoption of certain non-traditional advocacy models should be considered by advocates and paralegals when assisting victims, provided that the paramount consideration remains the best interests of the victims as survivors of sexual violence